(untitled) (Studia Prawnicze / The Legal Studies, 2022)
W artykule autor analizuje „stosowanie i „przestrzeganie” konstytucji, na tle naruszeń Konstytucji RP, mających miejsce po 2015 r. W toku tych naruszeń zacierane są granice między oboma pojęciami albo jedno pojęcie „wchłania” drugie. Autor przywołuje przypadki, kiedy to organ państwa przypisuje sobie kompetencję do przestrzegania konstytucji, ale wtedy gdy nie służy mu norma kompetencyjna (spoczywa zaś na nim obowiązek przestrzegania przepisu). Istota takiego przesunięcia normy kompetencyjnej między jedną a druga sferą polega na tym, że władza nie może nie przestrzegać konstytucji. Sama władza decyduje w ten sposób, co jest przestrzeganiem, a co jest nieprzestrzeganiem konstytucji. W sytuacji, w której nieprzestrzegania konstytucji nie daje się stwierdzić, najważniejszym aktem w systemie staje się ustawa, nie zaś konstytucja. Pojęcie przestrzegania konstytucji ma sens wówczas, gdy funkcjonuje hierarchiczny system norm prawnych. W takim przypadku odnajduje się sens podziału na stosownie oraz przestrzeganie konstytucji. The article explains the relation between the application and observance of the Constitution of the Republic of Poland in the context of violations of the Constitution. A characteristic feature of the normative model for the categories of ‘applying’ and ‘observing’ the law is that they are logically separate, but at the same time interrelated. After 2015, the relation between these concepts changed so as to transfer the competence norm from the sphere of application of the Constitution (where it logically belongs) to the sphere of observance of the Constitution, i.e. where an organ has an ordinary duty to execute the law (when it has no competence). It is a conceptual change which leads to a redefinition of the concept of ‘observing’ the Constitution. As a result of this change, the organ whose competence is to apply the Constitution now decides whether it is appropriate to observe the Constitution. This shifting of the competence norm between the two spheres means that the government cannot fail to abide by the Constitution, because the government itself determines what it means to observe it. The concept of ‘observing the Constitution’ makes sense only when there are independent reviewing institutions. In a situation where it is not possible to review whether the law is obeyed, the concept of observance loses its meaning.